Analisis Pendidikan Karakter Berdasarkan Kemampuan Awal Mahasiswa Jurusan PAI - Maisuhetni, Maisuhetni (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2022)
This study was a dercriptive qualitative research that aimed to analyze the character education based on the prior knowledge of the Second Semester students of Islamic Religion Education (PAI) Study Program in the Institute Islamic Religion (IAI) Tafaqquh Fiddin Dumai Study Year 2021/2022. The object of this research were 23 students of PAI Study Program in IAI Dumai. The students were group according to the prior knowledge i.e high, middle and low those are determined by the Middle Semester Examination (UTS) mark. The data collection tools tha we used were questionnaire, observation sheet and interview those are compiled based on the 18 value of character education, i.e: (1) religious, (2) honest, (3) tolerance, (4) discipline, (5) hard work, (6) creative, (7) independent, (8) democratic, (9) curiosity, (10 ) national spirit, (11) love the homeland, (12) appreciate achievements, (13) friendly or communicative, (14) love peace, (15) love to read, (16) care about the environment, (17) care about social, and (18) responsibility. Based on the data analysis relut obtain the average score of the questionnaire for students with high prior knowledge is 36.5, higher than the average score for the questionnaire for students with medium prior knowledge, which is 31.0 and higher than the average score of the questionnaire for students with low prior knowledge, which is 31.9. This study concludes that character education is directly proportional to students' prior knowledge.